Vascular smooth muscle cell-derived SO2 sulphenylated interferon regulatory factor 1 to inhibit VSMC senescence - Qiu, Bingquan; Zhang, Shangyue; Ge, Shuang; Yu, Zhengyu; Wang, Deqing; Li, Kun; Yu, Xiaoqi; Tang, Chaoshu; Du, Junbao; Jin, Hongfang; Huang, Yaqian (Frontiers in Pharmacology, 2025)
BackgroundVascular smooth muscle cell (VSMC) senescence is a critical driver of vascular aging and various age-related cardiovascular diseases. Endogenous sulfur dioxide (SO2), a newly identified key cardiovascular gaseous signaling mediator, accelerates collagen deposition and vascular remodeling in VSMCs when downregulated. However, its effects on VSMC senescence remain unclear.ObjectiveThis study focused on exploring the role of endogenous SO2 in VSMC senescence and its associated molecular pathways.MethodsAged mice (24 months old), VSMC-specific aspartate aminotransferase 1 (AAT1) knockout (VSMC-AAT1-KO) mice, D-galactose (D-gal)-treated aorta rings and rat VSMC line A7r5 were used in the experiments. AAT1 expression was detected by Western blot and single-cell RNA sequencing. Senescence markers Tp53, p21Cip/Waf, interleukin 1β (IL-1β) and IL6 expression were detected by Western blot and real-time quantitative PCR. Senescence-associated β-galactosidase (SA-β-gal) activity was detected using SA-β-gal staining kit. Sulphenylation of interferon regulatory factor 1 (IRF1) was detected using a biotin switch assay. The plasmid for mutant IRF1 (mutation of cysteine 83 to serine, C83S) were constructed by site-directed mutagenesis.ResultsThe expression of AAT1, a key enzyme for SO2 production, was reduced in the aortic tissue of aged mice in comparison to young mice. VSMC-AAT1-KO mice exhibited elevated protein expression of senescence markers Tp53, p21Cip/Waf and γ-H2AX in the aortic tissue. AAT1 knockdown in VSMCs elevated expression of Tp53, p21Cip/Waf, IL-1β and IL-6, and enhanced SA-β-gal activity. While SO2 donor supplementation rescued VSMC senescence caused by AAT1 knockdown and blocked aortic ring aging induced by D-gal. Mechanistically, SO2 promoted IRF1 sulphenylation, inhibited IRF1 nuclear translocation, which in turn downregulated the expression of senescence markers and the activity of SA-β-gal. Furthermore, mutation of C83 in IRF1 abolished SO2-mediated IRF1 sulphenylation and blocked the inhibitory effect of SO2 on VSMC senescence.ConclusionReduction of the endogenous SO2/AAT1 pathway played a crucial role in driving VSMC senescence. Endogenous SO2 counteracted VSMC senescence and vascular aging via the sulphenylation of IRF1 at C83.